An isothermal analysis of curved-vane and flat-vane swirlers for burners. Issue 3 (5th May 2015) - Parra-Santos, Teresa; Pérez-Domínguez, J.R.; Szasz, R.Z.; Castro-Ruiz, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – One current trend in burner technology is to obtain high efficiency while keeping low levels of NOx emissions. A swirling flow in combustion ensures a fixed position of a compact flame. Therefore, it is necessary to design efficient swirlers. Flow patterns are simulated for the different swirl devices proposed in this work. Two axial-swirlers are studied: one based on curve-vanes consisting of a straight line with an arc of a circle as the trailing edge and the other is the common flat-vanes. The purpose of this paper is to assess the accuracy of different swirl generators using a well-known benchmark test case. Design/methodology/approach – This work deals with modelling the swirler using two approaches: the general purpose Computational fluid dynamics (CFD) solver Ansys-Fluent® and the suite of libraries OpenFOAM® to solve the Reynolds Averaged Navier Stokes equations, showing there is a slight deviation between both approaches. Their performance involves analyzing not only the Swirl number but also the size of the recirculation zones in the test chamber. A subsequent process on the flow patterns was carried out to establish the intensity of segregation which provides insight into the quality of mixing. Findings – CFD models are feasible tools to predict flow features. It was found that numerical results tend to reduce the inner recirculation zone (IRZ) radial size. Further, an increase of the swirl number involves larger IRZ and a smaller outer recirculation zone (ORZ). The curved swirler displays a better axi-symmetric behaviour than flat vanes. There is weak influence of the chord vanes on the swirl number. The number of vanes is a compromise of head loses and guidance of the flow. Originality/value – The paper offers two different approaches to solve turbulent swirling flows. One based in a general contrasted commercial tool and other using open source code. Both models show similar performance. An innovative set up for an axial swirler different from the conventional flat vanes was proposed.